Penerapan Teknik Anyam Motif Bunga Cengkeh pada Ready to Wear - Annisa Kurnia Utami; Ariyana Damayanti; Romadhona Chusna Tsani (Garina, 2026)
Indonesia is an archipelagic country that has a diversity of ethnic groups as well as a rich heritage of arts and culture. One form of art found is weaving with clove flower motifs. The purpose of this study is “The Application of Clove Flower Motif Weaving Technique on Ready to Wear.” The main material used is shoelaces, as a weaving material that is easy to shape and unique. The method applied is Research and Development (R&D), which includes: identifying potential and problems, data collection through literature study, observation, documentation, product design, design validation, to the process of making and evaluating the final product. The results of the study show that the clove flower motif weaving technique can be well applied to ready to wear, especially on the vest and pants parts, producing a modern fashion. Applying this technique requires high precision, especially in the process of arranging the weaving pattern and integrating it with the main material. This study is expected to serve as a reference in developing innovative designs. The conclusion of this research is that the weaving technique gives a unique and aesthetic impression on ready to wear. The suggestion for making woven products applied to ready to wear is that during the process of ironing glue on the weave, the heat should not be too high because the shoelace material is easily burned, and the ends of the weave should be burned to prevent fraying.